Pod skrzydlatym znakiem „Albatrosa”: tłumaczenia Poego i Whitmana a rozwój serbskiej awangardy - Aćamović, Bojana (Przekłady Literatur Słowiańskich, 2021)
The paper aims to examine Serbian translations of Whitman and Poe published by the representatives of the 1920s avant-garde movements and to point to the place of these translations in the context of the developing Serbian modernism. A special focus is on the book series “Albatross”, a short-lived but important project of Belgrade avant-gardists, which significantly influenced the course of Serbian literature.